TUG‘RUQ JAROHATLARI – TURLARI VA OLDINI OLISH USULLARI - Tilyavova Sitora Amirzoda, Kamolova Zarnigor, Davronova Durdona (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is devoted to providing detailed information about the changes in the mental and emotional states of pregnant women before and after childbirth and birth injuries. In it, the conditions before and after childbirth are interpreted as urgent problems